Arthroscopically-assisted Reduction and Internal Fixation (ARIF) of tibial plateau fractures: clinical and radiographic medium-term follow-up - Leigheb, Massimiliano; Rusconi, Mattia; De Consoli, Antonio; Fredo, Massimiliano; Rimondini, Lia; Cochis, Andrea; Pogliacomi, Francesco; Grassi , Federico Alberto (Acta Biomedica Atenei Parmensis, 2020)
Background and Aim of the work: Tibial plateau fractures include a wide spectrum of lesions withpotentially disabling sequelae. Arthroscopically-assisted Reduction and Internal Fixation (ARIF) is an alternativeto traditional ORIF. The aim of this retrospective single centre study is to evaluate medium-term clinical andradiographic outcomes achieved in a consecutive series of patients treated with ARIF. Methods: 21 patients, with a mean age of 52.2 ± 13.4 years at surgery, were included. According to Schatzker classification, there were 9 type II, 10 type III, 2 type IV fractures. Associated intra-articular injuries (meniscal tears, tibial spine fractures, chondral lesions) were detected in 8 patients. At follow up, patients were clinically and radiographically evaluated according to knee ROM, KOOS, OKS and Rasmussen Clinical and Radiological Scores. Results: At an average follow-up of 84 ± 22.5 months, 18 patients were evaluated. Mean values recorded were the following: knee ROM 1° - 135°, OKS 41.6 / 48 ± 8.18, subscale KOOS scores ranged from 75% ± 25.4 (Quality of Life) to 91.1% ± 11.2 (Pain), Rasmussen Clinical e Radiological 27.2 ± 2.64 (14 excellent, 3 good, 1 fair) and 9.1 ± 0.64 (15 excellent, 3 good) respectively. Worse results were observed in 5 patients with pre-existing degenerative chondropathy. Conclusions: ARIF revealed to be an effective technique for surgical treatment of unicondylar tibial plateau fractures. Our findings support the favourable results reported by other authors. ARIF is not a simple technique and requiresspecific experience in knee arthroscopy and a steep learning curve.(www.actabiomedica.it)